Elastic and plastic characterization of a new developed additively manufactured functionally graded porous lattice structure: Analytical and numerical models. (May 2019) - Mahbod, Mahshid; Asgari, Masoud
Highlights: AM functionally graded porous lattice structure created based on a new developed double pyramid dodecahedron. Efficient analytical relations are derived in order to estimate the mechanical properties. Finite element analysis and experimental test were performed to validate the analytical relations. Functionally graded porosity is proposed to achieve desired distribution of properties and interesting crushing behaviour. Effects of geometrical features and graded distribution of porosity on the elastic and plastic behaviour are investigated. Abstract: In this paper, an additive manufactured functionally graded porous lattice structure created based on a new developed double pyramid dodecahedron is introduced. Analytical relations are derived in order to estimate the mechanical properties including elastic modulus, yield stress and Poisson's ratio of the proposed structures. Finite element models and experimental tests are also performed to validate the analytical solution which shows very well agreement. Plastic behavior of the proposed structures is investigated via explicit dynamic finite element method. The results showed good agreement between different approaches. Moreover the effect of geometrical features of unit cell on the mechanical properties of structures with different porosity is investigated. A functionally graded porosity is proposed in order to achieve desired graded distribution of properties as well as better crushing behavior. It was found that elastic modulus and yield stress are considerably dependent on the ratio of the length of the inclined struts to that of the uninclined ones. Furthermore, it is demonstrated that desirable values of mechanical properties could achieve in each layer by considering different trends of porosity in structures.